The self-efficacy of private school teachers toward the implementation of inclusive education in Ghana: A mixed-methods study - Opoku, Maxwell Peprah; Nketsia, William; Mohamed, Ahmed H. (Frontiers in Education, 2022)
Background: Although efforts towards practicing inclusive education have stalled in countries such as Ghana, the available data have mainly centred on enacting inclusive education in public schools. With private schools being notable alternative service providers to public schools, understanding private school teachers’ perceived self-efficacy towards teaching students with disabilities in the classroom is essential. Method: To develop insights into inclusive practices, a two-phase mixed-methods design was adopted for this study. In the first phase, 82 teachers from six private schools responded to the self-reported Teacher Efficacy for Inclusive Practice (TEIP) scale. In the second phase, there were 10 participants, including principals (n = 3), heads of department (n = 4) and teachers (n = 3). While the quantitative data were subjected to confirmatory factor analysis, t-tests, analysis of variance and linear regression, the qualitative data were analysed thematically using the components of the TEIP scale as a priori themes. Result: The study confirmed the structural validity of the TEIP scale in measuring teachers’ self-efficacy and the correlations and covariances between efficacy in managing behaviour and performing instruction and collaboration. There was divergence between the quantitative and qualitative data and background variables, such as educational qualifications, pre-service training in inclusive education and participation in professional development, which provided additional insights into the teachers’ self-efficacy. Conclusion: The findings show that some private school teachers teach students with disabilities despite having no confidence in their capabilities. The study findings underscore the need to create more training opportunities for private school teachers to enhance their confidence in practicing inclusive education in schools.